2016
DOI: 10.1007/s00426-015-0731-4
|View full text |Cite
|
Sign up to set email alerts
|

Ocular drift along the mental number line

Abstract: We examined the spontaneous association between numbers and space by documenting attention deployment and the time course of associated spatial-numerical mapping with and without overt oculomotor responses. In Experiment 1, participants maintained central fixation while listening to number names. In Experiment 2, they made horizontal target-direct saccades following auditory number presentation. In both experiments, we continuously measured spontaneous ocular drift in horizontal space during and after number p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 60 publications
2
35
1
Order By: Relevance
“…Eye movement recording yields access to the infant's mind or provides information about specific task strategies that cannot be extracted from response times or error rates alone (Bahnmueller et al, 2016;Ganor-Stern and Weiss, 2016;Macci Cassia et al, 2016;Van't Noordende et al, 2016). Moreover, the studies reported here shed new light on the temporal development of spatial-numerical associations during single number processing and arithmetic performance (Hartmann et al, 2016;Myachykov et al, 2016;Yu et al, 2016). The findings of these latter studies point toward an even richer role of eye movement research within the cognitive sciences.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Eye movement recording yields access to the infant's mind or provides information about specific task strategies that cannot be extracted from response times or error rates alone (Bahnmueller et al, 2016;Ganor-Stern and Weiss, 2016;Macci Cassia et al, 2016;Van't Noordende et al, 2016). Moreover, the studies reported here shed new light on the temporal development of spatial-numerical associations during single number processing and arithmetic performance (Hartmann et al, 2016;Myachykov et al, 2016;Yu et al, 2016). The findings of these latter studies point toward an even richer role of eye movement research within the cognitive sciences.…”
Section: Discussionmentioning
confidence: 65%
“…Loetscher et al (2010) showed that eye gaze position in the dark drifts rightward and upward when relatively larger numbers (i.e., numbers preceded by a smaller number) are called out in a random number generation task; similarly, the participant's gaze drifts leftward and downward for relatively small numbers). In this issue, Myachykov et al (2016) show that such numberinduced ocular drifts occur even then when participants fixate a central visual stimulus on the screen (Experiment 1) or when they are engaged in an additional saccade task (Experiment 2), suggesting that the processing of numerical magnitudes leads to inescapable interference with eye movement control (a phenomenon they labelled oculomotor resonance effect). Further evidence for such interference between semantic and oculomotor mechanisms comes from Ranzini et al (2016, this issue), showing that voluntary leftward and rightward eye movements (during smooth or stepwise pursuit of lateral targets) modulate the processing of number magnitudes in a parity judgment task.…”
Section: Development and Impairments Of Number Conceptsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent research into the cognitive representations of apparently abstract 1 concepts is consistent with embodied approach: for example, representations of the concepts denoting emotional valence (Foroni and Semin, 2009), time (Bottini et al, 2015), and number (Myachykov et al, 2016) were shown to be intimately linked with the perceptual experiences associated with their acquisition and use. Supporting this claim, several studies demonstrated that regular spatial-conceptual mappings accompany processing of words or symbols with numerical (Fischer, 2003; Fischer et al, 2004), spatial (Richardson et al, 2003), emotional (Meier and Robinson, 2004), and temporal (Núñez and Cooperrider, 2013) semantics.…”
mentioning
confidence: 79%
“…For example, the use of an internal, oriented, spatial continuum to represent number was demonstrated by showing that judgments about small numbers are faster when performed with the left hand, and judgments about large numbers are faster when performed with the right hand—the so-called SNARC effect (Spatial-Numerical Association of Response Codes; Dehaene, Bossini, & Giraux, 1993), and the processing of numerical magnitude influences the deployment of visual attention in space, with small numbers speeding up leftward relative to rightward orienting and the converse for larger numbers (e.g., Myachykov, Ellis, Changelosi, & Fischer, 2016). Similar spatial biases have been reported in the classification of such varied stimuli as visual shapes (e.g., Ren, Nicholls, Ma, & Chen, 2011), temporal events (e.g., Vallesi, Binns, & Shallice, 2008), pitches of sounds (e.g., Rusconi, Kwan, Giordano, Umiltà, & Butterworth, 2006), months of the year or days of the week (e.g., Gevers, Reynvoet, & Fias, 2003), letters of the alphabet (e.g., Gevers et al, 2003), and even elements in a learned list of unrelated words (e.g., Previtali, de Hevia, & Girelli, 2010; Van Opstal, Fias, Peigneux, & Verguts, 2009).…”
Section: Introductionmentioning
confidence: 99%